IDENTIFIKASI PENYAKIT DEGENERATIF DI DESA TANJUNG PULE KECAMATAN INDRALAYA UTARA KABUPATEN OGAN ILIR - Fadillah, Arif; ‘Ulhaq, Habibilah; Maharani, Meilia; Holil, Musaddad; Nadia, Nadia; Hasanah, Nur Kumalawati; Rusdi, Nyayu Fauziah; Aisyiyah, Putri; Madona, Sarli; Juwita, Tia; Putri, Tri Adista (Jurnal Abdimas Musi Charitas, 2025)
Purpose: This community service activity aimed to increase public awareness and encourage early detection of degenerative diseases, which are increasingly prevalent in Indonesia, particularly among the elderly population. The program was conducted in Tanjung Pule Village, North Indralaya District, to address the lack of public knowledge and limited health check practices related to non-communicable diseases such as diabetes, hypertension, and high uric acid levels. Design/Methodology/Approach: The program was carried out through a combination of health education and free medical check-ups. The methods included community outreach, distribution of health leaflets, and health screenings measuring blood pressure, blood glucose, uric acid, and cholesterol levels using EasyTouch® GCU devices. The activities were conducted in collaboration with the local health post and village authorities. Findings: The program engaged 30 participants and revealed that more than 50% had elevated levels of uric acid and cholesterol. The health education sessions were well-received, with participants demonstrating increased awareness of symptoms, causes, and prevention strategies. These findings indicate a significant need for continuous health monitoring and preventive interventions in the community. Practical Implications: The outcomes of this program can serve as a practical model for other rural areas facing similar health issues. It emphasizes the importance of integrating education with basic health services to promote community-driven health awareness and disease prevention. Originality/Value: This initiative uniquely combines preventive screening with targeted education in a rural setting, addressing an underrepresented issue in community health outreach. The program contributes to reducing barriers to health access and reinforces the role of universities in supporting local public health efforts.